Penafsiran Ayat-Ayat Tidur Sebagai Kematian Kecil Dalam Kitab Tafsir Mafatih Al-Ghaib - Muh Fatihuddin (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2022)
Sleep is a very important activity for human life, sleep itself is a state in which the spirit is grasped by God and returned when he awakens, and has similarities with the death that is both held by God. In the Qur'an there are many verses about sleep that equate to death. This study discusses sleep as a small death perspective of the Qur'an using his analysis Fakhr al-Di@n al-Ra>zi@ in the book of Mafa>ti@h{ al-Ghayb. The author found that there are two verses that are in accordance with the research, namely in surat al-An'a>m verse 60 and az-Zumar verse 42. From the results of the study revealed that sleep is a condition in which a person's sense of taste is lost from the body so that the sense of birth does not perform activities. And sleep is also a state in which God grasps the spirit of a person who sleeps and is restored upon awakening. Sleep is a type with dead that distinguishes is if the person who sleeps his spirit is cut off imperfectly, while when in a dead position his spirit is cut off perfectly. According to other mufassir that sleep is a condition in which his spirit can meet with other spirits it is not separated from god's will. Related to all that is a super natural thing that must be believed. While the implication of the interpretation is a person who is in a state of sleep he is still burdened with abomination, and doing it is when he has awakened. And there is no obligation to compensate when someone is in a sleep condition doing damage.